Porphyromonas gingivalis deteriorates autism spectrum disorders by disturbing the gut and oral microbiota - Li, Bosheng; Qiao, Yanan; Li, Yongming (Frontiers in Microbiology, 2025)
Autism spectrum disorder (ASD) significantly impairs socialization and communication, posing a major societal challenge due to limited understanding of its pathogenesis and lack of effective treatments. Recent studies have shown an imbalance in the oral and intestinal microbiota of individuals with ASD, which may exacerbate ASD symptoms. In this study, we successfully established an ASD mouse model induced by Porphyromonas gingivalis (Pg) solution. Bio-behavioral experiments, including the elevated plus maze test, demonstrated that Pg. induced anxiety-like behaviors in mice. Analysis of oral and intestinal microbiota revealed significant alterations in microbial richness, diversity, and evenness in Pg-treated mice, indicating that Pg. disrupted the normal bacterial community structure and function. Subsequent 16S rRNA sequencing showed increased abundance of amino acid metabolism pathways in Pg-intervened mice, highlighting the close link between bacterial community function and carbohydrate, amino acid, and nucleotide metabolic pathways. These findings provide promising clinical targets for ASD treatment and offer insights into developing new therapeutic strategies.